Medical Yoga Therapy - Ina Stephens (MDPI AG, 2017)
Medical yoga is defined as the use of yoga practices for the prevention and treatment of  medical conditions. Beyond the physical elements of yoga, which are important and effective for  strengthening  the  body,  medical  yoga  also  incorporates  appropriate  breathing  techniques,  mindfulness, and meditation in order to achieve the maximum benefits. Multiple studies have  shown that yoga can positively impact the body in many ways, including helping to regulate blood  glucose levels, improve musculoskeletal ailments and keeping the cardiovascular system in tune. It  also has been shown to have important psychological benefits, as the practice of yoga can help to  increase mental energy and positive feelings, and decrease negative feelings of aggressiveness,  depression and anxiety.